Direct sequence spread spectrum: history, principles and modern applications - Stojanović, Nenad M.; Todorović, Branislav M.; Ristić, Vladimir B.; Stojanović, Ivana V. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Direct sequence spread spectrum modulation is widely used in many radiocommunications systems. At the first time, this modulation technique was used in military communications and navigation systems. Later, applications became diverse in civil communication systems as well. Today, there are many systems where direct sequence spread spectrum modulation is implemented as a part of the system. This article aims to sublimate knowledge about the direct sequence spread spectrum modulation technique and its applications. Methods: The article presents a review of the historical development of the direct sequence spread spectrum modulation technique, its principles and the most important current applications. Results: Based on a large number of references, this article summarizes the historical development, basic principles and modern applications of the direct sequence spread spectrum modulation in military and commercial communication systems. Conclusion: Direct sequence spread spectrum modulation is widely used in modern wireless and satellite radiocommunications. It is expected to be part of future global communication systems.